Global, regional, and national burdens of MDR-TB attributable to smoking from 1990 to 2021 with a prediction from 2022 to 2050 - Dan, Du; Lei, Zhang; Xue, Wen; Ze-Xin, Liu (Frontiers in Public Health, 2025)
ObjectiveThe aim was to offer a comprehensive epidemiological assessment of the global prevalence and the smoking-related Multidrug-resistant tuberculosis (MDR-TB) disease burden from 1990 to 2021 and to forecast the trends in smoking burden over three decades.MethodsWe compared the burden of smoking-related MDR-TB and temporal trends by gender, age, socio-demographic index (SDI), region, and country. Forecasting analyses of the changing trend in the burden of smoking-related MDR-TB up to 2050 was conducted based on the ARIMA model and ES models.ResultsThe global age-standardized rate (ASR) of smoking-related MDR-TB increased from 1990 to 2021, highlighting a significant disease burden. In 2021, the cumulative Disability adjusted life years (DALYs) attributed to MDR-TB tallied up to 239,707 cases, with Lesotho, Uzbekistan, Kyrgyzstan, bearing the brunt. The likelihood of developing MDR-TB rose as individuals advanced in years, manifesting most acutely among men aged 35–39 in lower SDI and Low-middle SDI regions. Predictive analysis suggests that by 2050, deaths and DALYs of smoking-related MDR-TB, as well as their corresponding ASR, will continue to decrease.ConclusionThe burden of MDR-TB worldwide, adjusted for age, and related to smoking, has shown a decline from 1990 to 2021. However, regional disparities have been identified, with some areas experiencing an increase in this burden. These regions with a higher burden emphasize the necessity for the implementation of strong tobacco control measures.